Feasibility of passive bistatic geosynchronous radar using comsat transmissions - Hobbs, Stephen; Convenevole, Carlo; Gashinova, M.; Cherniakov, M.; Cassidy, S. (IEEE, 2018)
Communication satellites in geosynchronous orbit are increasingly broadcasting digital signals with high bandwidth and high power. These signals are in principle well-suited to radar imaging and the study presented here is an initial feasibility study for a passive bistatic synthetic aperture radar using satellites in geosynchronous orbit (GEO). The persistent viewing possible from GEO could enable important new applications. The mission concept is outlined and studies of the available signal formats identify digital TV broadcasts in Ku-band as most suitable for radar imaging. The additional space hardware required is a dedicated receive channel, which could be implemented as a hosted payload at modest cost. Our findings so far suggest that the mission concept is feasible for coarse spatial resolution images and that it could therefore provide a low-cost technology demonstration of geosynchronous radar.
Keywords: bistatic; radar; geosynchronous; passive; comsat